Reliability and Validity of The Family Needs Scale In A Turkish Population. Issue 5 (4th September 2013) - Bilgin, Sonay; Coban, Gulay Ipek; Tanriverdi, Derya
Abstract: Aims and objectives: This study aimed to adapt an English version of the survey tool Family Needs Scale (FNS) for Turkish patients and to evaluate its psychometric properties. Background: Social care providers can reduce the risk for dysfunction in low‐income families of preschoolers and increase resilience by responding to needs identified by the families themselves. Quality instruments developed to identify family needs within this population are scarce. To measure the needs of families with disabled children effectively, valid and reliable instruments that are sensitive to parents' expectations and to the constructs of nursing must be used. Conclusions: Nine factors were detected in the results, Cronbach's α reliability coefficient was .95 and item–total point correlations were between .32–.81. In addition, it was found that the test–retest correlation value was .91, which was found to be statistically significant ( p < .001). Relevance to clinical practice: This scale can be used in nursing research projects to evaluate family needs regarding the care of children with a disability.